2017
DOI: 10.1002/anie.201702473
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Single Iron Atoms Anchored on N‐Doped Porous Carbon as an Efficient Electrocatalyst for the Oxygen Reduction Reaction

Abstract: The development of low-cost, efficient, and stable electrocatalysts for the oxygen reduction reaction (ORR) is desirable but remains a great challenge. Herein, we made a highly reactive and stable isolated single-atom Fe/N-doped porous carbon (ISA Fe/CN) catalyst with Fe loading up to 2.16 wt %. The catalyst showed excellent ORR performance with a half-wave potential (E ) of 0.900 V, which outperformed commercial Pt/C and most non-precious-metal catalysts reported to date. Besides exceptionally high kinetic cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
1,008
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,701 publications
(1,075 citation statements)
references
References 34 publications
33
1,008
1
3
Order By: Relevance
“…While this divacancy-based moiety has been explored theoretically for its intriguing electronic, magnetic and catalytic properties 43,44 , it's never been fully identified experimentally, which seriously hampers its fundamental and applied investigations. We note that although several previous experimental studies suggested the divacancy-based MN 4 C 4 moiety 11,12,45,46 , there was insufficient spectroscopic evidence to verify its existence, as such structural assignments were mainly based on EXAFS spectra and none of the previously reported EXAFS spectra could well match with the simulated standard spectra of the divacancy-based MN 4 C 4 moiety (Supplementary Fig. 27).…”
Section: Nature Catalysismentioning
confidence: 80%
“…While this divacancy-based moiety has been explored theoretically for its intriguing electronic, magnetic and catalytic properties 43,44 , it's never been fully identified experimentally, which seriously hampers its fundamental and applied investigations. We note that although several previous experimental studies suggested the divacancy-based MN 4 C 4 moiety 11,12,45,46 , there was insufficient spectroscopic evidence to verify its existence, as such structural assignments were mainly based on EXAFS spectra and none of the previously reported EXAFS spectra could well match with the simulated standard spectra of the divacancy-based MN 4 C 4 moiety (Supplementary Fig. 27).…”
Section: Nature Catalysismentioning
confidence: 80%
“…HER is a combination of proton adsorption on catalyst surface via Volmer reaction (H + + e − + * → H*, where * refers to catalysts surface) followed by desorption of H 2 through either Tafel reaction (2H* → H 2 + 2*) or Heyrovsky reaction (H + + e − + H* → H 2 + *). [13][14][15]18] Based on these results we constructed a molecular model of SACs for hydrogen adsorption energy calculation including all possible active sites, namely, graphitic-N, graphitic-C, pyridinic-N, terminal pyridinic-N, pyrrolic-N, and N-oxide species. The free energy change for hydrogen adsorption on the catalyst surface (ΔG H *) determines the kinetics of the HER.…”
Section: Theoretical Activity Prediction Of Sacs For Hermentioning
confidence: 99%
“…[41] However, in order to prevent the agglomeration, credible supports for the uniform distribution of SAs are imperatively needed. [43] ZIF-8 was chosen as cages to separate and encapsulate Fe(acac) 3 which served as SA precursor. Specifically, the Zn-contained bimetallic ZIFs-derived carbon materials have proved promising for SA stabilization, because Zn ions could spatially attenuate the concentration of requisite metal ions, and the evaporation of Zn will generate uncoordinated N atoms, which could serve as coordination sites to bind with SAs.…”
Section: Single Atoms@mof-derived Nanostructuresmentioning
confidence: 99%